Definitions and Concepts of Organizational Sustainability: A Literature Analysis - Rahman, Mostafizur; Abd Wahab, Dr. Sazali; Abdul Latiff, Dr. Ahmad Shaharudin (Society & Sustainability, 2022)
This research paper provides a comprehensive literature review that thoroughly examines the definitions and different concepts of organizational sustainability. This paper also looks at how research gaps are addressed in the literature with a particular emphasis on issues of organizational sustainability. Overall, organizational sustainability, including issues and aspects related to sustainability, is discussed. Individual authors provide their perspectives on various aspects of organizational sustainability from their field research, case analysis, and creative search. It also includes a greater knowledge of how real economic activity concerns and political dynamics can inhibit decision-making related to operational or practical sustainability. Several sustainability viewpoints from around the world have provided a genuine mechanism for organizations to increase their financial success while minimizing their impact on the environment and society. This study urges that knowing an organization's ability to change and self-regulate on critical issues for long-term sustainability can help solve the socio-ecological dilemma. This study shows how firms approach sustainability and what fundamental issues still need to be resolved. The research has provided novel and unusual insights into the factors contributing to organizational sustainability. Additional value is generated by estimating progress toward the idea of organizational sustainability, identifying impediments, and analyzing various real-world examples of measures to enhance advancement toward that concept.